Quality of Life and Job Performance of Employees of a Construction Company in Doha, Qatar, during the 2022 FIFA World Cup - Arendon, Ryan Anthony M.; Briones, Jesus; Baldovino, Flormando P. (Inclusive Society and Sustainability Studies, 2023)
Hosting mega-sport events is a risk-involving decision, but the intangible benefits as an outcome cannot be ignored. This study gauged the impact of the 2022 FIFA World Cup on the quality of life through the working conditions, public safety, and cost of living related to the job performance of the 20 finance and accounting department workforce of a construction company in Doha, Qatar. Employing the descriptive-correlation method as the research design, the data gathered using the researcher-structured questionnaire were analyzed using frequency, percentage, weighted mean, and Spearman Rho coefficient correlation test as statistical tools. The study concluded that the anticipated negative quality of life indicators did not materialize during the mega-sport event. Further, the 2022 FIFA World Cup did not negatively impact the respondents' job performance since they still managed to perform their job assignments well. The paper, therefore, encourages that, at the very least, employees to diligently perform their jobs at all times while employers provide the necessities and should always consider safeguarding their employees' quality of life while at work by providing decent and comfortable working conditions and reasonable compensation and benefits enabling them to adequately cover their cost of living, especially during periods where mega-events are to be held within the geographical scope of their business operations. This study is useful for policymakers who are planning to utilize mega events to enhance the quality of life and job performance of working residents of the host communities.